2020
DOI: 10.1155/2020/1583132
|View full text |Cite
|
Sign up to set email alerts
|

Study on Software Vulnerability Characteristics and Its Identification Method

Abstract: A method for identifying software data flow vulnerabilities is proposed based on the dendritic cell algorithm and the improved convolutional neural network to effectively solve the transmission errors in software data flow. In this method, we first gave the software data flow propagation model and constructed the data propagation tree structure. Secondly, we analyzed the running characteristics of the software, took the interaction among indexes into account, and identified data flow vulnerabilities using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…For memory deallocation primitive, the mutation space of its parameter addr contains the addresses of all the allocated and deallocated chunks in the current state. For the writing primitive, the mutation space of its parameter addr contains the addresses to be controlled in the target state (the definition of target state will be given later), and the mutation space of width is the set [1,2,4,8,16,32,64,128]. en, we input these mutated MOPs into the heap allocator model one by one and process them according to the mapping relationship to obtain the final new program state.…”
Section: Heap Allocator Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…For memory deallocation primitive, the mutation space of its parameter addr contains the addresses of all the allocated and deallocated chunks in the current state. For the writing primitive, the mutation space of its parameter addr contains the addresses to be controlled in the target state (the definition of target state will be given later), and the mutation space of width is the set [1,2,4,8,16,32,64,128]. en, we input these mutated MOPs into the heap allocator model one by one and process them according to the mapping relationship to obtain the final new program state.…”
Section: Heap Allocator Modelmentioning
confidence: 99%
“…Since cyberattacks have severely damaged the quality of software [1,2], considerable defensive schemes have been taken to protect software security [3,4]. In recent years, due to the deployment of mitigation mechanisms for stack-based vulnerabilities and compiler-level inspections, stack exploits have become increasingly more difficult to execute against hardened programs [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…While the former can constitute a potential loophole in information systems security [9], [10], faulty software development in utilizing the appropriate security requirements represents the core weakness in the landscape of information system security. According to Luo et al [11], such weaknesses are "defects in software's specific implementation or system security policy, which can enable attackers to access or damage the system without authorization".…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the context of this study, the work reported in [12] discussed students' software development knowledge at a more general level. However, current literature suggests that there has been more emphasis on improving students' programming skills and optimising teaching programming techniques [13][14][15]. But scanty investigations tend to probe students' awareness of emergent security challenges and the state-of-the-art software development principles designed to guarantee secure systems development.…”
Section: Introductionmentioning
confidence: 99%